Interventions to Improve Uptake of Direct-Acting Antivirals for Hepatitis C Virus in Priority Populations: A Systematic Review - Ortiz-Paredes, David; Amoako, Afia; Ekmekjian, Taline; Engler, Kim; Lebouché, Bertrand; Klein, Marina B. (Frontiers in Public Health, 2022)
Background & Objective Access to Hepatitis C (HCV) care remains suboptimal. This systematic review sought to identify existing interventions designed to improve direct-acting antiviral (DAA) uptake among HCV infected women, people who inject drugs (PWID), men who have sex with men (MSM), and Indigenous peoples. Methods Studies published in high- and middle-income countries were retrieved from eight electronic databases and gray literature (e.g., articles, research reports, theses, abstracts) were screened by two independent reviewers. Identified interventions were summarized using textual narrative synthesis. Results After screening 3,139 records, 39 studies were included (11 controlled comparative studies; 36 from high-income countries). Three groups of interventions were identified: interventions involving patients; providers; or the healthcare system. Interventions directed to patients included care co-ordination, accelerated DAA initiation, and patient education. Interventions involving providers included provider education, telemedicine, multidisciplinary teams, and general practitioner-led care. System-based interventions comprised DAA universal access policies and offering HCV services in four settings (primary care, secondary care, tertiary care, and community settings). Most studies (30/39) described complex interventions, i.e., those with two or more strategies combined. Most interventions (37/39) were tailored to, or studied among, PWID. Only one study described an intervention that was aimed at women. Conclusions Combining multiple interventions is a common approach for supporting DAA initiation. Three main research gaps were identified, specifically, a lack of: (1) controlled trials estimating the individual or combined effects of interventions on DAA uptake; (2) studies in middle-income countries; and (3) interventions tailored to women, MSM, and Indigenous people.